PERAN LITERASI DIGITAL DALAM MEMPENGARUHI NIAT BERBAGI PENGETAHUAN DI DUNIA MEDIS - Desi Pakadang; Yoke Pribadi Kornarius; Angela Caroline; Agus Gunawan (Journal of Innovation Research and Knowledge, 2025)
Sharing knowledge in the medical field is crucial as it can enhance patients care quality and accelerate their recovery. An individual's proficiency in technology can motivate them to share their knowledge more extensively. However, medical staff often exhibit low digital literacy, as it is not typically considered a core competency in their careers. This study employed a survey method involving 122 medical staff at a hospital. Data was analyzed using regression testing to verify the influence of digital literacy on the intention to share knowledge. The results indicated that individuals with high digital literacy are more inclined to share their knowledge, benefiting the organization. Additionally, individuals with significant work experience demonstrated lower digital literacy compared to those with moderate experience. Organizations can use this research as a reference to design technology skills training programs that are more accessible to senior employees.